Evolutionary Algorithm-based Feature Selection for an Intrusion Detection System - Singh, D. K.; Shrivastava, M. (Engineering, Technology & Applied Science Research, 2021)
Keeping computer reliability to confirm reliable, secure, and truthful correspondence of data between different enterprises is a major security issue. Ensuring information correspondence over the web or computer grids is always under threat of hackers or intruders. Many techniques have been utilized in intrusion detections, but all have flaws. In this paper, a new hybrid technique is proposed, which combines the Ensemble of Feature Selection (EFS) algorithm and Teaching Learning-Based Optimization (TLBO) techniques. In the proposed, EFS-TLBO method, the EFS strategy is applied to rank the features for choosing the ideal best subset of applicable information, and the TLBO is utilized to identify the most important features from the produced datasets. The TLBO algorithm uses the Extreme Learning Machine (ELM) to choose the most effective attributes and to enhance classification accuracy. The performance of the recommended technique is evaluated in a benchmark dataset. The experimental outcomes depict that the proposed model has high predictive accuracy, detection rate, false-positive rate, and requires less significant attributes than other techniques known from the literature.